Multidimensional Synergy in Employee Performance Escalation: Analysis of Leadership Roles, Work Environment, and Motivation - Daspar Daspar; Zulfa Zakiatul Hidayah; Novi Fitria Hermiati; Shafiera Lazuarni; Annisa Aulia Aryani (Economics and Digital Business Review, 2026)
The importance of employee performance as a primary factor in determining an organization's success amid increasingly competitive business environments. Employee performance is a key factor in determining an organization's success and sustainability; therefore, a more comprehensive understanding of the factors that influence it is necessary. To achieve optimal performance, organizations need to consider various influencing factors, including leadership, the work environment, and motivation. The purpose of this study is to further investigate how leadership, the work environment, and motivation impact improvements in employee performance. A mixed-methods approach was used. Primary data were collected via questionnaires and interviews with experts, while secondary data were obtained from articles and other reference materials. The population comprised of working students enrolled at Pelita Banga University in Bekasi Regency. The sample was selected using accidental sampling. Structural Equation Modeling (SEM) was employed as the statistical analysis method using SmartPLS software. The results indicate that leadership has a positive effect on employee performance, the work environment has a positive effect on employee performance, and motivation has a positive effect on employee performance.